Vila Nova: entre sonhos, grades e sobrevivência - Ferreira, Flavia de Melo Leonel (2018)
This research deals with the reality of the territorial context of the Vila Nova neighborhood in the municipality of Registro-SP. In the face of complexities we perceived, we sought to reflect on how particular are the expressions of social issues in that territory. Therefore, a brief literature review on the capitalist mode of production and the production and reproduction of unequal social relations was necessary. Within this discussion it was possible to think the role that the state plays in this context. The territory was presented through data, participant observation and research subjects’ narratives, which enabled an analysis of the social locus that it takes in the municipality and in the capitalist system. It reveals a territory affected by poverty, stigma, limited or no access to rights, police violence and a high incarceration rate. By discussing the relationship between the state and "social issues" through the life stories of the research subjects, it is possible to reconcile macro- and micro-level analysis presenting how this relationship occurs both in the broader capitalist context and in the particular context of Vila Nova and considering the conditions for the high incarceration rate of its residents. In the narratives of the subjects, the potentialities and possibilities of the territory become evident, demonstrating that Vila Nova is a place of many struggles and resistances